Knockdown of growth differentiation factor-15 restrains prostate cancer through regulating MAPK/ERK signaling pathway: GDF15 affects prostate cancer via MAPK/ERK - Yang, Minggen; Guo, Miaolin; Su, Chenqiang; Hao, Weiping; Xu, Zhenqiang (Cellular and Molecular Biology, 2024)
Prostate cancer, prevalent among males, is influenced by various molecular factors, including Growth Differentiation Factor 15 (GDF15). Despite its recognized role in multiple tumor types, GDF15's specific involvement in prostate cancer remains insufficiently explored. This study investigates the regulatory function of GDF15 in prostate cancer. To explore GDF15's impact, we established GDF15 knockdown and overexpression models in prostate cancer cells. We quantified mRNA and protein levels using RT-PCR and Western blotting. Functional assays, including CCK8, Transwell, wound healing, and flow cytometry, were employed to evaluate cell proliferation, invasion, migration, and apoptosis. Additionally, the effect of GDF15 on tumor growth was assessed using a metastatic tumor model in nude mice. Elevated GDF15 expression was identified in prostate cancer tissues and cells. The knockdown of GDF15 led to the activation of the MAPK/ERK signaling pathway. C16PAF was found to counteract the inhibitory effects of sh-GDF15 on cell proliferation, invasion, migration, and apoptosis in LNCaP cells. It also reversed the sh-GDF15-induced alterations in the epithelial-mesenchymal transition (EMT) process. In vivo, C16PAF notably mitigated the sh-GDF15-induced suppression of tumor growth. The study demonstrated that sh-GDF15 inhibits cell proliferation, invasion, migration, EMT process, and tumor growth, while it promotes apoptosis. However, these effects were significantly reversed by C16PAF. The study underscores the potential of GDF15 as a target for novel therapeutic interventions in prostate cancer treatment and prevention. These findings illuminate GDF15's multifaceted role in prostate cancer pathogenesis and suggest its viability as a therapeutic target.